ACTION PLAN DAN STRATEGI PENDIDIKAN DASAR DI KABUPATEN BEKASI - Andi Sopandi; Kurniawati Mulyanti; Rusham .; Yayat Suharyat; Bujang .; A. Fachrurozi (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2006)
Decentralization of education has provided the base of information on what happens in the sector of education as the consequences of regional autonomy. The policy of decentralization for primary and middle-level education has been commenced since 2001, by handing over the authority for running the management of the education to the local government at sub-urban and municipal level.